Wasted! Resource recovery and waste management in Cuba - Michael Ahlheim; Maike Becker; Yeniley Allegue Losada; Heike Trastl (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
The collection of solid waste and the recovery of recyclable material from waste belong to the many challenges Cuba has been facing over the past years. In this paper, we give a short account of the actual waste situation and analyze the causes of the obvious deficiencies of the waste sector. We conducted a small survey in Havana city in order to assess peoples awareness of the garbage problem, their appraisal of the actual situation and their willingness to contribute personally to an improvement of the waste situation. Based on the insights gained from this survey and from our theoretical analysis of the Cuban waste management we develop suggestions for an improvement of the waste situation in Cuba. These suggestions take into account that the financial means available for a reform of the waste management system in Cuba are severely restricted. Therefore, our suggestions are more focused on organizational and motivational changes than on the introduction of high technology.
urn:nbn:de:bsz:100-opus-15416
Keywords: H4; I31; Q53; Q28; 330; Waste Management; Recycling; Incentive; Contingent Valuation; Cuba